Meningkatkan Kemampuan Mengolah Angka Dan Menghitung Secara Manual Pada Anak-Anak Disaung Baca Suradita-Kp.Suradita Rt 004/001,Desa Suradita,Kec Cisauk ,Kab Tangerang,Banten 15343 - Santa Anggel Maranata Mc Halley; Septi Sri Wahyuni; Febri Lestari; Wiwit Irawati; Maulidina Fitria (Universitas Pamulang, 2022)
Education to children about improving the ability to process numbers and calculate manually using the Jarimatika method. During the pandemic, elementary school children are not allowed to go to school and face to face directly at school by the Indonesian government. To improve understanding of the concept of processing numbers and assist students in solving addition, subtraction, and multiplication problems. This is based on factual condition where students have not been able to work on the number multiplication and also the monotonous learning methods implemented made learning mathematics feels difficult. This service is carried out collaboratively with the supervisors and administrators of Saung Baca Suradita, Cisauk in understanding activities, processing numbers and counting manually using the Jarimatika method. The purpose of this service is to help students think creatively in learning mathematics with the Jarimatika method. In addition, the provision of information on number recognition and the fingering method was carried out using blackboards and posters. Keywords: Educations; Jarimatika